Magnetic Resonance Imaging versus Proton Magnetic Resonance Spectroscopy in Neonatal Hypoxic Ischemic Encephalopathy in Egyptian Population: Pilot study - Ossama Y Mansour; Doaa Hanfy; Sameh Fathy; Rania E Mohammed (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
Background: Hypoxic-ischemic encephalopathy (HIE) is a serious condition that results of critical failure of the intrapartum gas exchange and may lead to a signifi cant damage in the central nervous system. Objective: to elucidate the role of brain magnetic resonance imaging (MRI) versus Proton magnetic resonance spectroscopy (1H-MRS) in the diagnosis and evaluating the severity of HIE in full-term Egyptian neonates Design: 49-months observational controlled study. Setting: Pediatric neurology and Radiology Departments, Alexandria University Hospital         Patients and Methods: Thirty full-term neonates in the fi rst two weeks with HIE (Sarnat staging) were included (18 males and 12 females), with exclusion of those with congenital brain malformation and/ or perinatal infection in addition to 15 age- and sex- matched healthy controls. All patients and controls were examined with brain MRI and 1H-MRS. Results: In neonates with HIE, the percent of agreement between clinical staging, and MRI grading was 66.67 while it was 76.67 regarding 1H-MRS grading. The sensitivity for MRI was 66.67%, specifi city was 75%, accuracy was 77.78%, PPV was 80% and NPV was 75%. Meanwhile, the sensitivity for 1H-MRS was 92%, specifi city was 75%, accuracy was 84.44%, PPV was 82.14% and NPV was 88.24%. Conclusion: 1H-MRS detected more percent of agreement, true positive and less false negative cases than MRI. Despite the equal specifi city between them, still 1H-MRS got more sensitivity, accuracy, PPV and NPV than MRI i.e. when we have to choose early and single investigation it is recommended to choose 1H-MRS.